Main modelling features of the ASTEC V2.1 major version. (July 2016) - Chatelard, P.; Belon, S.; Bosland, L.; Carénini, L.; Coindreau, O.; Cousin, F.; Marchetto, C.; Nowack, H.; Piar, L.; Chailan, L.
Highlights: Recent modelling improvements of the ASTEC European severe accident code are outlined. Key new physical models now available in the ASTEC V2.1 major version are described. ASTEC progress towards a multi-design reactor code is illustrated for BWR and PHWR. ASTEC strong link with the on-going EC CESAM FP7 project is emphasized. Main remaining modelling issues (on which IRSN efforts are now directing) are given. Abstract: A new major version of the European severe accident integral code ASTEC, developed by IRSN with some GRS support, was delivered in November 2015 to the ASTEC worldwide community. Main modelling features of this V2.1 version are summarised in this paper. In particular, the in-vessel coupling technique between the reactor coolant system thermal-hydraulics module and the core degradation module has been strongly re-engineered to remove some well-known weaknesses of the former V2.0 series. The V2.1 version also includes new core degradation models specifically addressing BWR and PHWR reactor types, as well as several other physical modelling improvements, notably on reflooding of severely damaged cores, Zircaloy oxidation under air atmosphere, corium coolability during corium concrete interaction and source term evaluation. Moreover, this V2.1 version constitutes the back-bone of the CESAM FP7 project, which final objective is to further improve ASTEC for use in Severe Accident Management analysis of the Gen.II–III nuclear power plants presently under operation or foreseen in near future in Europe. As part of this European project, IRSN efforts to continuously improve both code numerical robustness and computing performances at plant scale as well as users' tools are being intensified. Besides, ASTEC will continue capitalising the whole knowledge on severe accidents phenomenology by progressively keeping physical models at the state of the art through a regular feed-back from the interpretation of the current and future experimental programs performed in the international frame.